2017
DOI: 10.1088/1758-5090/9/1/015023
|View full text |Cite
|
Sign up to set email alerts
|

Validation of scaffold design optimization in bone tissue engineering: finite element modeling versus designed experiments

Abstract: This study reports the development of biological/synthetic scaffolds for bone tissue engineering (TE) via 3D bioplotting. These scaffolds were composed of poly(L-lactic-co-glycolic acid) (PLGA), type I collagen, and nano-hydroxyapatite (nHA) in an attempt to mimic the extracellular matrix of bone. The solvent used for processing the scaffolds was 1,1,1,3,3,3-hexafluoro-2-propanol. The produced scaffolds were characterized by scanning electron microscopy, microcomputed tomography, thermogravimetric analysis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 89 publications
2
46
0
Order By: Relevance
“…(ii) The typical distribution of the von Mises stresses within the scaffold model displays the presence of stress peaks in the proximity of the point where the generic strand enters in contact with the strand of the adjacent layer ( Figure 11). This same mechanical behavior was reported by Uth et al [34] who observed peaks of stress in alignment with the filaments of the previous layer.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…(ii) The typical distribution of the von Mises stresses within the scaffold model displays the presence of stress peaks in the proximity of the point where the generic strand enters in contact with the strand of the adjacent layer ( Figure 11). This same mechanical behavior was reported by Uth et al [34] who observed peaks of stress in alignment with the filaments of the previous layer.…”
Section: Discussionsupporting
confidence: 88%
“…Materials 2020, 13,648 17 of 21 the strand of the adjacent layer ( Figure 11). This same mechanical behavior was reported by Uth et al [34] who observed peaks of stress in alignment with the filaments of the previous layer. (iii) The amounts of bone predicted with the proposed algorithm are comparable with those predicted with other scaffolds based on different unit cell geometries [36,38,40,41].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Bone grafts and substitutes are used in millions of operations worldwide . Nevertheless, these therapies pose the risk of infection, immune response, disease transfer, or stress shielding . Tissue engineering is an alternative approach for the repair of damaged tissues and organs .…”
Section: Introductionmentioning
confidence: 99%